PENGARUH MUTASI TERHADAP SEMANGAT KERJA APARATUR SIPIL NEGARA DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN MALUKU TENGGARA BARAT - Matrutty, Kevin Janis; TULUSAN, FEMMY; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2019)
The research has been intended to identify and analyze how a mutation affect theworkforce of the workforce and the development of human resources in the western region ofmaluku. The method that the writer USES in this study is the asosiative research method basedon a positivism philosophy, used by researchers in a particular population or sample. Samplingof samples used is accindendal sampling techniques of research in the body's department andthe development of human resources in maluku southwest of the west of 33. Analysis of dataanalysis is simple regression analysis and simple korelation analysis. Based on coronalcorelation analysis (r) = 0.848 means the correlation of the two variables are positive andsignificant. Based on simple regression analysis got the y = 8.667 + 0,722 which means therelationship between the two variables is positive. Whereas from the testing initiative ofdeterminations, the PFF was extracted by.0,72 or 72%. With the result it can be explained thatthe contribution to the spirit of work is 72% while the rest isa contribution to the other.According to the results of the initial test, f 79,379 was made to f table by 2.60 to the point of0.05. From the data it's got f is counting bigger than the f table where fcount 79,379 > 2.60.Then ho was rejected and ha received. It means that there is an influence between the variablesof a mutation in the environment of the workforce and the development of human resources inthe western region of maluku.Key Words: Mutations, Labor, Civil State Apparatus